2014
DOI: 10.1136/bmj.g1838
|View full text |Cite
|
Sign up to set email alerts
|

Revolutionising management of chronic disease: the ParkinsonNet approach

Abstract: Patients with Parkinson’s disease need long term support to manage their condition. Bastiaan Bloem and Marten Munneke describe the benefits of a model of integrated care provided by a network of specialists and suggest it has promise for other long term conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(122 citation statements)
references
References 23 publications
1
115
0
6
Order By: Relevance
“…14 In the Netherlands, the Parkinson's disease registry not only tracks strains on care givers as well as patient-and clinician-reported outcomes, it involves patients, families, physicians, and clinical scientists in developing guidelines to promote a consistently high standard of care. 12 In the United States, the ImproveCareNow network for inflammatory bowel disease engages patients and families alongside care teams and scientists in its design, governance, and operation, 15 enabling improved sensitivity to what matters to patients. Thus, though the registry had initially focused on measuring simple remission rates, partnering with patients revealed that patients and their families were more interested in prolonged, steroid-free remissions, which have improved from 55% to 78% in participating practices.…”
Section: Unmet Potentialmentioning
confidence: 99%
“…14 In the Netherlands, the Parkinson's disease registry not only tracks strains on care givers as well as patient-and clinician-reported outcomes, it involves patients, families, physicians, and clinical scientists in developing guidelines to promote a consistently high standard of care. 12 In the United States, the ImproveCareNow network for inflammatory bowel disease engages patients and families alongside care teams and scientists in its design, governance, and operation, 15 enabling improved sensitivity to what matters to patients. Thus, though the registry had initially focused on measuring simple remission rates, partnering with patients revealed that patients and their families were more interested in prolonged, steroid-free remissions, which have improved from 55% to 78% in participating practices.…”
Section: Unmet Potentialmentioning
confidence: 99%
“…via educational programs), and technology is used to facilitate communication and collaboration. Interprofessional collaboration is facilitated through regional network meetings and a web-based communication platform [6,130]. The aim of ParkinsonNet is to deliver high quality, individualized and integrated care to PwP and their families.…”
Section: Pd Expertisementioning
confidence: 99%
“…In the Netherlands, PD care is organized in regional networks that consist of highly dedicated and specifically trained healthcare professionals in the field of PD: the ParkinsonNet approach [6,130]. Care is organized not in silos but in integrated networks, patients are engaged as partners in the healthcare process (e.g.…”
Section: Pd Expertisementioning
confidence: 99%
“…In this regard, the authors propose episodic ‘boost’ rehabilitations or a less intensive maintenance treatment in an outpatient setting by community-based therapists, possibly by adopting the Dutch ParkinsonNet approach 6. Such possibilities must be explored using inpatient rehabilitation followed by controlled washouts with various types of maintenance treatments.…”
Section: We Discuss the Tremendous Challenges To Reliably Demonstratementioning
confidence: 99%